Factors Affecting Commuters' Intentions in Using Park and Ride (P&R) Facilities Based on Theory of Planned Behavior - Irawati, Sara; Widyawati Agustin, Imma; Rini Dwi Ari, Ismu (Civil and Environmental Science Journal (CIVENSE), 2022)
Park and Ride (P&R) is a form of transportation demand management closely related to commuting activities. Several developed countries, such as the UK, Canada, China, and Hong Kong already implemented P&R with a high level of effectiveness and success in overcoming the congestion problems in the city center, low use of public transportation, and air pollution. However, in developing countries, the various positive impacts of P&R still have not been able to encourage commuters' intentions to use these facilities. The level of P&R use at Sidoarjo Station is still relatively low (44.3%). Behavioral is one of several keys to the success of P&R that depends on intention and ability. The intention is the result of knowledge, social, and infrastructure that can support the use of public transport and P&R. This study aims to identify factors that can influence commuters' intentions to use P&R at Sidoarjo Station based on the theory of planned behavior using SEM analysis. The results showed that P&R and public transportation conditions as perceived behavioral control were the most influential factors on commuter intentions. The conditions of public transportation (including availability and location) and the quality of P&R facilities are also essential considerations for commuters using P&R.